Empowerment of Community Based Tourism Group in Bonjeruk Village through Training on Herbal Lotion Production - Rozikin, Rozikin; Azhar, Abdillah Adipatria B.; Utary, Dewi; Zoraya, Sabrina Intan; Setyaningrum, Tri Wahyu (Jurnal Ilmiah Pengabdian dan Inovasi, 2026)
Bonjeruk Tourism Village in Central Lombok is rich in local biodiversity, including citronella (Cymbopogon citratus) and coconut-based products (VCO), which have high potential as herbal tourism commodities. However, the tourism awareness group (Pokdarwis) has not yet optimized these natural resources into standardized products. This community service program aims to strengthen the capacity of Pokdarwis through training on the production of standardized herbal anti-mosquito and UV-protective lotion. The activities included education on herbal formulation, hands-on production training, SOP development, branding, and introduction of product legality. A total of 22 participants attended the program. Pre- and post-assessment showed a significant increase in participants’ knowledge, particularly regarding the benefits of herbal ingredients (from 45.45% to 68.18% in the “strongly agree” category), hygiene practices (13.64% to 40.91%), and confidence in independently producing herbal lotion (18.18% to 50%). Following the completion of the program, the Pokdarwis Bonjeruk and community members were able to independently conduct mass production of two raw materials (Virgin Coconut Oil/VCO and citronella oil) and herbal lotion. The products are actively used by local farmers and gardeners for daily outdoor activities, particularly for protection against ultraviolet exposure and mosquito bites. Furthermore, the products have been commercialized and sold to both domestic and international tourists. Positive feedback from foreign tourists indicates strong acceptance of the products’ aroma, texture, and perceived benefits